Battle of Thermopylae: 300 Spartans (natural killer cells plus obinutuzumab) versus the immortal warriors (chronic lymphocytic leukemia cells) of Xerxes’ army - García-Muñoz, Ricardo (Future Sci OA, 2019)
AIM: To analyze the effects of subcutaneous or intravenous rituximab + lymphokine-activated killer cells, obinutuzumab or ibrutinib on natural killer (NK) cell levels in chronic lymphocytic leukemia and follicular lymphoma patients. PATIENTS & METHODS: The distribution of peripheral blood NK cells of 31 patients was analyzed by flow cytometry. RESULTS: We detected a decrease of NK cells in peripheral blood below normal range after obinutuzumab treatment. During maintenance treatment with subcutaneous rituximab, an NK cell reduction was less pronounced than after intravenous rituximab treatment, despite lymphokine-activated killer cell infusions. CONCLUSION: After one dose of obinutuzumab, each NK cell in peripheral blood destroys 25 leukemic cells.